Collaborative narrative coaching in medicine: a case study with a resident physician and a practicing emergency physician (Canadian Medical Education Journal, 2023)
In recent years, many postgraduate medical institutions are transitioning from a time-based model to competency based medical education (CBME). This paradigm shift offers many advantages but has also been criticized for its potentially reductionist approach of targeting competency as the end goal. In this context, coaching may be an interesting intervention as it has been employed with success in other professional settings to go beyond achieving competency with a focus on continuous development. Currently there is little published data on the effectiveness of this intervention in the medical field. Our study aims to describe a coaching intervention between two dyads of a coach and physician as well as analysing the repercussions of the intervention on their professional practice. Results of our study show the unique learning journeys of both dyads as well as the creation of value in each cycle for both participants. In conclusion, coaching in medicine is an interesting intervention with the potential to complement the existing medical training programs in order to achieve optimal professional development.